A competency framework for internal quality assurance in higher education. (2019) - Jingura, Raphael Muzondiwa; Kamusoko, Reckson
Quality assurance systems in higher education play a key role in supporting and improving the quality of educational services provided by Higher Education Institutions (HEIs). The role of Internal Quality Assurance (IQA) in higher education is now well-established. This paper considers the professional competencies of IQA practitioners in HEIs. The focus is on building a body of knowledge for IQA. The objective is to contribute a theoretical framework that supports professional development of IQA practitioners in HEIs. The competency framework is synthesised from information available in literature. The framework is made up of two parts. The first part provides a map of the key functions of IQA. There are nine domains of the functions. The scope of IQA work includes, amongst others, setting the regulatory framework, evaluation, auditing, reviewing and facilitating improvement. The map of functions serves as the reference point of the competency framework. The competency framework is based on the triad model of knowledge, skills and attitude. The framework has nine domains which include; knowledge, communication, managerial, analytical, digital, research, interpersonal, personal skills and attitude. This forms the body of knowledge for IQA. IQA practitioners need this competency repertoire in order to perform their functions effectively and efficiently.